Reproductive effects of subchronic exposure to acetamiprid in male rats - ERCAN, FERİHA (NATURE PUBLISHING GROUP, 2020)
Acetamiprid, a selective agonist of nicotinic acetylcholine recetors, is one of the most widely used neonicotinoids. There is limited data about toxicity of acetamiprid on male reproductive system. Therefore, the study aimed to investigate the reproductive toxic potential of acetamiprid in male rats orally treated with acetamiprid with low (12.5mg/kg) medium (25mg/kg) or high dose (35mg/kg) for 90 days. According to our results, sperm concentration and plasma testosterone levels decreased in dose dependent manner. Gonadotropin-releasing hormone (GnRH), follicle-stimulating hormeone (FSH), luteinizing hormone (LH) levels increased at low and medium dose groups and acetamiprid caused lipid peroxidation and glutathione (GSH) depletion in the testes. Histologic examinations revealed that acetamiprid induced apoptosis in medium and high dose groups and proliferation index dramatically decreased in high dose group. In conclusion, acetamiprid caused toxicity on male reproductive system in the high dose. The mechanism of the toxic effect may be associated with oxidative stress, hormonal disruptions and apoptosis.
Keywords: NIGELLA-SATIVA OIL; HORMONAL-REGULATION; OXIDATIVE STRESS; TOXICITY; TESTOSTERONE; MORPHOLOGY